Self Disclosure Pengguna Fitur Close Friend Pada Second Account Mahasiswa Di Kota Denpasar - Wulandari, I Gusti Ayu Laksmi Tri; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia (E-Jurnal Medium, 2025)
The development of social media today can also make it easier for users to communicate virtually through pictures, videos, or audio. With these advanced features, they are slowly starting to express themselves in social media. This can be seen from how some social media users begin to reveal themselves with a variety of expressions and begin to show skills that have never been shown before or what is currently referred to as self-disclosure. This study aims to determine how self-disclosure of close friend feature users on second account students in Denpasar City by applying descriptive qualitative research methods and constructivism paradigm. The data collection techniques used in this research are interviews and observations to the four informants with the help of the Johari Window Theory which consists of four parts including, open area, blind area, hidden area, and unknown area. The results showed that students in Denpasar City tend to do self-disclosure when using the close friend feature on their second Instagram account. Self disclosure that tends to be highlighted is the personality in the open area and hidden area. The close friend feature on the second account is used as a place to do self-disclosure because it is considered the most comfortable social media account to be yourself. the way that is done in showing personality also varies and varies.